IMPROVING STUDENTS’ UNDERSTANDING IN ENGLISH TEACHING AND LEARNING PROCESS BY USING CODE-SWITCHING - Syukriati Syukriati (Universitas Islam Negeri Mataram, 2016)
Sociolinguistics phenomenon such as code-mixing and code-switching commonly found in the bilingual and multilingual society, including in school and classroom area. Psychologically and naturally, bilingual and multilingual people tend to mix and switch their code or language in order to have intended messages and effective purposes of communication. Code-switching is mostly found in the English teaching and learning activities in Indonesia at almost every level. Teacher and students need to switch their codes into their mother tongues or their second languages in order that the “difficult” English features could be learnt and comprehended well. Therefore, instead of avoiding code-switching and the use of the learners’ mother tongues as the instuctional language, the teachers are recommended to use and organize as effectively as possible the L1 and code-switching in deliberating English material to establish and improve students’ understanding in English. It is believed that code-switching may have psycological and pedagogical effects to motivate students to have linguistic competence.